Toward the use of precision medicine for the treatment of head and neck squamous cell carcinoma - Gong, Wang (Oncotarget, 2016)
Precision medicine is a new strategy that aims at preventing and treating human diseases by focusing on individual variations in people's genes, environment and lifestyle. Precision medicine has been used for cancer diagnosis and treatment and shows evident clinical efficacy. Rapid developments in molecular biology, genetics and sequencing technologies, as well as computational technology, has enabled the establishment of “big data”, such as the Human Genome Project, which provides a basis for precision medicine. Head and neck squamous cell carcinoma (HNSCC) is an aggressive cancer with a high incidence rate and low survival rate. Current therapies are often aggressive and carry considerable side effects. Much research now indicates that precision medicine can be used for HNSCC and may achieve improved results. From this perspective, we present an overview of the current status, potential strategies, and challenges of precision medicine in HNSCC. We focus on targeted therapy based on cell the surface signaling receptors epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF) and human epidermal growth factor receptor-2 (HER2), and on the PI3K/AKT/mTOR, JAK/STAT3 and RAS/RAF/MEK/ERK cellular signaling pathways. Gene therapy for the treatment of HNSCC is also discussed.